Diagnostic conundrums in antenatal presentation of a skeletal dysplasia with description of a heterozygous C‐propeptide mutation in COL1A1 associated with a severe presentation of osteogenesis imperfecta. Issue 12 (23rd August 2016) - Marshall, Charlotte J.; Arundel, Paul; Mushtaq, Talat; Offiah, Amaka C.; Pollitt, Rebecca C.; Bishop, Nicholas J.; Balasubramanian, Meena
Abstract : Prompt and accurate diagnosis of skeletal dysplasias can play a crucial role in ensuring appropriate counseling and management (both antenatal and postnatal). When a skeletal dysplasia is detected during the antenatal period, especially early in the pregnancy, it can be associated with a poor prognosis. It is important to make a diagnosis in antenatal presentation of skeletal dysplasias to inform diagnosis, predict prognosis, provide accurate recurrence risks, and options for prenatal genetic testing in future pregnancies. Prenatal ultrasound scanning is a useful tool to detect several skeletal dysplasias and sonographic measurements serve as reliable indicators of lethality. The lethality depends on various factors including gestational age at which features are identified, size of the chest and progression of malformations. Although, it is important to type the skeletal presentation as accurately as possible, this is not always possible in an antenatal presentation and it is important to acknowledge this uncertainty. In the case of a live birth, it is always important to reassess the infant. Osteogenesis imperfecta (OI) is a heterogeneous group of disorders characterized by fragile bones. Here, we report an infant with severe OI born following a twin pregnancy in whom the bone disease is caused by a heterozygous pathogenic mutation, c.4160C >T, p.(Ala1387Val) located in the C‐propeptide region of COL1A1 . An assumption of lethality antenatally complicated his management in early life. We discuss this patient with particular emphasis on the neonatal presentation of a severe skeletal dysplasia and the lessons that may be learned in such situations. © 2016 Wiley Periodicals, Inc.